2022
DOI: 10.1002/smll.202107225
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Integrate Iron Single Atom and Nanocluster Triggered Tandem Effect for Boosting Oxygen Electroreduction

Abstract: Atomically nitrogen‐coordinated iron atoms on carbon (FeNC) catalysts are emerging as attractive materials to substitute precious‐metal‐based catalysts for the oxygen reduction reaction (ORR). However, FeNC usually suffers from unsatisfactory performance due to the symmetrical charge distribution around the iron site. Elaborately regulating the microenvironment of the central Fe atom can substantially improve the catalytic activity of FeNC, which remains challenging. Herein, N/S co‐doped porous carbons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 52 publications
(61 reference statements)
1
53
0
Order By: Relevance
“…NC has the united rhombic dodecahedron shape with the mean size of ∼ 400 nm, which is in agreement with that of ZIF-8. Since the N atoms doped in NC could function as anchors to adsorb MnAc molecules, NC successfully adsorbed MnAc in isopropanol solution to form MnAc/NC ( Huo et al, 2020 ; Qu et al, 2021 ; Zhai et al, 2022 ), which was then further pyrolyzed at 900°C. The obtained black power was washed by 3 M HCl solution to etch the unstable metal particles, then annealed again at 900°C for 1 h in N 2 condition to recover the crystallinity, forming Mn-N x /NC which possesses highly-dispersed Mn-N x active sites.…”
Section: Resultsmentioning
confidence: 99%
“…NC has the united rhombic dodecahedron shape with the mean size of ∼ 400 nm, which is in agreement with that of ZIF-8. Since the N atoms doped in NC could function as anchors to adsorb MnAc molecules, NC successfully adsorbed MnAc in isopropanol solution to form MnAc/NC ( Huo et al, 2020 ; Qu et al, 2021 ; Zhai et al, 2022 ), which was then further pyrolyzed at 900°C. The obtained black power was washed by 3 M HCl solution to etch the unstable metal particles, then annealed again at 900°C for 1 h in N 2 condition to recover the crystallinity, forming Mn-N x /NC which possesses highly-dispersed Mn-N x active sites.…”
Section: Resultsmentioning
confidence: 99%
“…When the Tafel slope is greater than 100 mV dec −1 , the RDS is the formation of the OH* intermediate in the first electron transfer step. 61,155,156…”
Section: Applications Of Fe-sacsmentioning
confidence: 99%
“…When the Tafel slope is greater than 100 mV dec À1 , the RDS is the formation of the OH* intermediate in the first electron transfer step. 61,155,156 Research results showed that when Fe, Co, and Ni are used as catalysts, the OER catalytic effect follows the order of Ni 4 Co 4 Fe. According to DFT calculation, it was found that N doping will cause the redistribution of the charge of the carbon material.…”
Section: Fe-sacs For Energy Storagementioning
confidence: 99%
“…catalysts [ 11–15 ] have received significant attention thanks to their maximum atom utilization efficiency, adjustable electronic configurations, and excellent catalytic performance. [ 16–24 ] Particularly, Fe–N–C catalysts, predominantly comprising with Fe‐N 4 sites, deliver remarkable significant ORR activity and selectivity. [ 25–28 ] Nevertheless, significant performance disparity still exists between Fe–N–C catalysts and platinum‐group‐based catalysts, on account of the symmetric electron distribution in Fe–N 4 active sites result in unsuitable free energy for the adsorption/desorption of oxygen intermediates and in turn badly decrease the kinetic activity.…”
Section: Introductionmentioning
confidence: 99%